2012
DOI: 10.1029/2011jd017102
|View full text |Cite
|
Sign up to set email alerts
|

A reassessment of the budget of formic and acetic acids in the boundary layer at Dumont d'Urville (coastal Antarctica): The role of penguin emissions on the budget of several oxygenated volatile organic compounds

Abstract: [1] Initiated in 1997, the year-round study of formic and acetic acids was maintained until 2011 at the coastal Antarctic site of Dumont d'Urville. The records show that formic and acetic acids are rather abundant in summer with typical mixing ratios of 200 pptv and 700 pptv, respectively. With the aim to constrain their budget, investigations of their potential marine precursors like short-chain alkenes and acetaldehyde were initiated in 2011. Acetic acid levels in December 2010 were four times higher than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(100 citation statements)
references
References 69 publications
(81 reference statements)
9
91
0
Order By: Relevance
“…Measurements of acetaldehyde are sparse in Antarctic regions. As discussed by Legrand et al (2012), at the coastal site of DDU an acetaldehyde background mixing ratio close to 80 pptv can be assumed, though this value may be highly variable over the Southern ocean (5 to 50 pptv). Hamer et al (2007) reported a mixing ratio of CH 3 CHO of 60 pptv at the SP.…”
Section: Radical Sources and Sinksmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of acetaldehyde are sparse in Antarctic regions. As discussed by Legrand et al (2012), at the coastal site of DDU an acetaldehyde background mixing ratio close to 80 pptv can be assumed, though this value may be highly variable over the Southern ocean (5 to 50 pptv). Hamer et al (2007) reported a mixing ratio of CH 3 CHO of 60 pptv at the SP.…”
Section: Radical Sources and Sinksmentioning
confidence: 99%
“…For CH 3 COCH 3 a typical mixing ratio of 130 ± 30 pptv was used on the basis of observations made at the SP (Hamer et al, 2007). For CH 3 COOH, Legrand et al (2012) measured 60-70 pptv at Dome C between November and February.…”
Section: Radical Sources and Sinksmentioning
confidence: 99%
“…Since the recoveries are, however, not zero, OC determinations obtained with a UV method are only referred to as DOC if a sample filtration through a quartz fibre filter was applied prior to OC measurements. Whereas this procedure was applied by Hagler et al (2007a), all the other studies using UV methods (Federer et al, 2008;Twickler et al, 1986;Preunkert et al, 2011;Legrand et al, 2007aLegrand et al, , 2013 do not remove insoluble particles prior OC analysis.…”
Section: Toc or Doc ?mentioning
confidence: 99%
“…Sugar, levoglucosan, phenols and anthropogenic persistent organic compounds were measured in ambient aerosols at Mario Zucchelli Station and Concordia Station Barbaro et al, 2016Barbaro et al, , 2017Barbaro et al, , 2015a. Carboxylic acids with low molecular weights were also measured at Mario Zucchelli Station, Concordia Station, and Dumont d'Urville (Barbaro et al, 2017;Legrand et al, 2012).…”
Section: Introductionmentioning
confidence: 99%